Soft Magnetic Composites as Quantitative 3D Compression Sensors for Wearable Technology. Issue 3 (11th October 2021) - Miller, Jonathan D.; Cabarkapa, Dimitrije; Hermes, Matthew J.; Fry, Andrew C.; Berkland, Cory J.
Abstract: Detecting the magnitude of compression or shear events can provide valuable data to assess forces experienced by sensitive equipment or even the human body. Compression sensors have historically had limited use in fields such as wearable technology due to the large size of the sensors, lack of 3D sensing capacity, need for rigid components, or signal quality issues associated with the orientation or deformation of soft composites under compression. In particular, soft magnetic composites paired with a magnetometer to sense material deformation have been hindered by such issues. Here, experiments evaluated soft silicone‐magnetic powder composites of various shapes, sizes, magnetic filler concentrations, and orientations to a magnetometer to optimize sensor performance. Sensors with smaller diameter (≤2.5 mm) cylinder‐shaped magnetic elements exhibited a linear response to compression when paired with a 3 mm × 3 mm magnetometer. The soft magnetic elements composed of 80% magnetic powder by weight, the highest concentration tested, had the greatest sensitivity. Parameters from these studies are used to design a sensor integrated into a football helmet, which successfully recorded 3D force data from head impacts while being worn, demonstrating the potential for such sensors in wearable technology applications. Abstract : Silicone‐magnetic powder composites provide a platform for designing soft, low‐profile 3D force sensors for wearable technologies. Several experiments are performed to identify design parameters to optimize sensor sensitivity and accuracy. Resulting sensors are able to detect the duration and magnitude of force in 3 dimensions and perform properly in detecting head impacts in a football helmet.